Parenting styles and empathy in adolescents involved in cyberbull - Quintana Peña, Alberto (2013)
He present study aimed to analyze the relationship between parental socialization styles, the process of empathy and the phenomenon of cyberbullying, the scope expands beyond the physical boundaries of the school, being able to route from home to teenagers to digital scenes. In this regard we investigated students from public and private educational institutions of Punjab obtaining a sample of 560 adolescents of both sexes between 13 and 17 years old. This sample was administered the scale of parental socialization styles in adolescence (ESPA 29) that provides parental socialization styles of mother and father, the Interpersonal Reactivity Index (IRI), which measures the degree of empathy and Questionnaire of Cyberbullying (Calvete, E., Orue, I., Estevez, A., Villardón, and Padilla, P., 2009) that measures both the realization of cyberbullying as being a victim of cyberbullying. The Information was collected through a design-correlational descriptive, with a cluster sampling of the study population. Correlations were found between parental socialization styles and degree of empathy, and between the degree of empathy and participation in episodes of cyberbullying, whether in the role of victim or perpetrator of and found three of the four hypotheses, to while no significant correlations were found between parental socialization styles and participation in episodes of cyberbullying, rejecting the fourth hypothesis. We are having achieved most of the objectives in this research these results will contribute to the development of an intervention protocol in cyberbullying, which will facilitate the development of strategies to promote prosocial behaviors in the affected population.